Karakterisasi Morfologi dan Patogenisitas Colletotrichum sp. dan Lasiodiplodia sp. dari Daun Kelengkeng yang Terinfeksi Penyakit Anraknosa dan Bercak Daun di Merangin - Hibatullah, Juanita; Safitri, Mutia (Biospecies, 2026)
Longan Merangin Regency, Jambi Province. However, longan production is frequently constrained by is an economically important fruit crop widely cultivated in Indonesia, particularly in foliar diseases, notably anthracnose and blight, which significantly reduce both yield and fruit quality. This study aimed to isolate and identify the fungal pathogens associated with anthracnose and blight symptoms on longan leaves collected from Pulau Rengas, West Merangin. Symptomatic leaf samples were subjected to fungal isolation, followed by macroscopic and microscopic characterization. Pathogenicity assays were conducted in vitro to confirm the disease-causing potential of the isolates. Two distinct fungal species were identified: Colletotrichum sp., exhibiting gray, cottony colonies with septate hyphae and cylindrical conidia, and Lasiodiplodia sp., characterized by dark gray to black, fluffy colonies and ellipsoid to obovoid conidia. In vitro, inoculation of healthy longan leaves with these isolates resulted in the development of characteristic lesions: brownish-gray spots for Colletotrichum sp. and dark necrotic lesions for Lasiodiplodia sp., confirming their pathogenicity. These findings are consistent with previous reports implicating these genera as causal agents of anthracnose and blight in longan and other tropical crops. This study represents the first report of Lasiodiplodia sp. associated with blight spot disease in longan leaves.